Perennial Philosophy as a Critique of Modern Epistemological in the Thought of Seyyed Hossein Nasr - Dian Anggraini (Mahad Aly Al Fithrah, 2026)
This article aims to analyze perennial philosophy as a critique of modern epistemological exclusivism in the thinking of Seyyed Hossein Nasr. Modern epistemology, which is related to rationalism and empiricism, tends to place empirical reason as the only valid standard of truth. Thus, it limits the sources of knowledge to dimensions that are scientifically verified and objectively measured. This paradigm gives rise to epistemic reductionism and encourages the desacralization of knowledge by disregarding the metaphysical, intellectual-spiritual, and revelatory dimensions of the epistemic structure. In this context, modernity not only brings technological progress, but also a crisis of meaning rooted in the severing of the relationship between science and transcendent reality. This study uses a qualitative approach based on literature review with descriptive and philosophical-critical analysis methods, focusing on the major works of Seyyed Hossein Nasr, especially his book Knowledge and the Sacred. The results of this study show that perennial philosophy in Seyyed Hossein Nasr's thinking serves as a corrective critique of modern epistemological exclusivism. Through the concepts of scientia sacra and the hierarchical structure of knowledge, Seyyed Hossein Nasr offers a reintegration between reason, metaphysical intellect ('aql), and revelation as the ontological foundation of knowledge. The concept of scientia sacra is sacred science or sacred knowledge rooted in metaphysical reality and sourced from enlightened intellectual revelation ('aql). Therefore, perennial philosophy does not reject modern science, but rather corrects its epistemic reductionism and proposes the resacralization of science as a solution to the epistemological crisis of contemporary modernity